Young pregnant women from the perspective of three school physical education teachers (2019)
This qualitative exploratory study seeks to interpret the feelings, thoughts, and actions of three physical education teachers, based on their knowledge and decisions regarding cases of pregnant students. Teachers’ feelings, knowledge, and actions are found in activities and they are reflected in the students’ perceptions, which encourage them to think, understand, and give meaning to the class processes. The fieldwork included six non-participant observations described in a record sheet three times a week for five months. As a complement to this exercise, six semi-structured interviews were carried out based on two meetings with each participant. The results suggest that teachers act in accordance with disciplinary imperatives that privilege biophysical body care beyond sociocultural aspects, which is why they have made physical performance and motor development the main lines of their educational proposals.